2018
DOI: 10.1039/c8ra00711j
|View full text |Cite
|
Sign up to set email alerts
|

Towards selective electrochemical conversion of glycerol to 1,3-propanediol

Abstract: 1,3-propanediol (1,3-PD) is a bulk chemical with myriad applications in polymers, lubricants, cosmetics, foods industries and in the synthesis of heterocyclic compounds. Current commercial production of 1,3-PD involves a thermocatalytic process using acrolein (DuPont) and ethylene oxide (Shell) as starting feedstock. These feedstocks are petroleum-based and there are many efforts at using glycerol as low cost biomass-derived feedstock for 1,3-PD production. A number of catalyst designs and bacterial & fungal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…This limitation can be bypassed either by thermal or catalytic dehydration of neighboring hydroxy groups (see, e. g., Ref. [16]), or by an electrooxidation of the hydroxy group to a respective ketone or aldehyde, making the adjacent hydroxy groups accessible for subsequent reductive removal [15,17,18] . The products that are accessible by oxidation such as glyceraldehyde, glyceric acid, dihydroxyacetone, hydroxypyruvic acid, and tartronic acid (Scheme 1) make glycerol a promising key platform chemical [19] .…”
Section: Introductionmentioning
confidence: 99%
“…This limitation can be bypassed either by thermal or catalytic dehydration of neighboring hydroxy groups (see, e. g., Ref. [16]), or by an electrooxidation of the hydroxy group to a respective ketone or aldehyde, making the adjacent hydroxy groups accessible for subsequent reductive removal [15,17,18] . The products that are accessible by oxidation such as glyceraldehyde, glyceric acid, dihydroxyacetone, hydroxypyruvic acid, and tartronic acid (Scheme 1) make glycerol a promising key platform chemical [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these products are vastly valuable compounds (like glycolic acid, glyceric acid and lactic acid), others like dihydroxyacetone have a lower price in the market. The valu able compounds like 1,2 propanediol and 1,3 propanediol are the new potential products that have been achieved recently via glyc erol electro reduction reaction, where 1,3 propanediol has higher market price than 1,2 propanediol (James et al, 2018;Lee et al, 2018). Some products available from both glycerol electro oxidation and electro reduction reactions with their applications are listed in Table 1.…”
Section: Glycerol and Value-added Chemicals In The Market Prospectsmentioning
confidence: 99%
“…This can be considered as the technological heart of the upgrade kit, as it allows operation in a two-chamber system with physical separation of anodic oxidation and cathodic reduction. As polmyer-based membranes are commonly applied as separators in MES, the sterilization procedure was exemplified using a widely utilized cation exchange membrane (fumasep FKE) (e.g., Rozendal et al, 2008;Sevda et al, 2013;Jiang et al, 2017;Rosa et al, 2017;James et al, 2018). For preliminary tests in non-sterile conditions, it was shown that mechanical mounting of the membrane was sufficient.…”
Section: Sterilization Of the Inlay With Membranementioning
confidence: 99%